Aplikasi Penghitung Daya Listrik Sederhana berbasis Android - Wisnu Kartika (INTEGER: Journal of Information Technology, 2020)
At this time, electrical energy has been widely used in various fields. Electrical energy has been widely used in daily activities. Formulas and applications for calculating electric power have been widely used and developed. In this research, an Android application will be developed that can be used to calculate power by inserting the variable electrical energy used in a certain time. This application was developed using the MIT App Inventor 2. This application can run well. The conclusion of this research is that it can develop an Android-based power calculator application.